Main factors of monitoring and key participants in the implementation of strategic innovations in the construction sector - Gergi, D.; Yelin , V.; Grohol, V.; Ostapenko, I. (Ways to Improve Construction Efficiency, 2024)
The article is devoted to the analysis of the main factors of monitoring and key participants in the implementation of strategic innovations in the construction sector. The growing demand for innovative solutions in construction requires effective monitoring of technological changes and the implementation of innovative strategies to increase the competitiveness of construction enterprises. Special attention is paid to identifying the main factors influencing the success of innovations in the industry, such as the use of digital technologies, process automation, integration of new project management methods, as well as interaction between key participants - developers, contractors, investors and end users. Given the specifics of the construction industry, important factors are technological development, managerial flexibility, adaptability to market changes, as well as resource efficiency. Innovations in construction include both technological innovations and changes in organizational structures, financing methods, project management and interaction between participants. The article also focuses on the role of each participant in the process of implementing innovations, especially on how the interaction between project participants contributes to the effective implementation of construction tasks. The challenges faced by participants in implementing innovations are examined, and strategies for overcoming them are proposed. Important aspects are the assessment of risks arising from the implementation of innovations, as well as opportunities for reducing these risks by adapting strategic approaches to changing market conditions and technological innovations. In addition, the article draws attention to the importance of developing flexible management strategies that allow construction companies to quickly respond to new technological trends, minimizing costs and improving the quality of construction project implementation. The use of such strategies as adapting financing methods, using the latest technologies to control costs, and improving interaction between project participants is an important tool in achieving successful implementation of innovations in the construction sector.